Seribu Peta Citra Desa dan Pembangunan Pedesaan - Taryono Taryono; Agus Anggoro Sigid; Priyono Priyono (Proceedings Series on Social Sciences & Humanities, 2024)
This article discusses the importance of rural development planning supported by the availability of spatial data in the form of maps. The "1000 Village Maps" program is an initiative by the Faculty of Geography, Muhammadiyah University of Surakarta, to provide grants of village image maps to villages in Central Java and parts of East Java. The method of map creation involves students in various stages, from preliminary surveys to map handovers. The results and discussion of the article depict stories from several recipient villages, highlighting the appreciation and benefits felt by the village authorities, as well as the positive impact on development planning. This program is expected to enhance the quality of rural development planning and strengthen the bond between higher education institutions and communities through community service.